Impact of flavoured tobacco restriction policies on flavoured product availability in Massachusetts. Issue 2 (18th February 2019) - Kingsley, Melody; Song, Glory; Robertson, Jennifer; Henley, Patricia; Ursprung, W W Sanouri
Abstract : Objective: This study aimed to evaluate the effectiveness of flavoured tobacco product restriction policies in reducing availability of flavoured products in Massachusetts communities. Methods: Data were obtained from surveys of tobacco retailers conducted from July 2015 to March 2017. On a community level, flavoured product availability was defined as the per cent of retailers during a given 3-month quarter that sold flavoured cigars/cigarillos, electronic cigarettes and/or e-liquids. Communities that implemented the policy during the study period were grouped into wave 1 (n=18; 1481 retail surveys) and wave 2 (n=20; 483 retail surveys) by date of policy implementation; communities without a flavoured product restriction served as the control group (n=234; 4932 retail surveys). A difference-in-difference analysis was used to compare the change in flavoured product availability in wave 1 and wave 2 communities 3 months pre-policy and post-policy implementation to the change over the same time periods in the control group. Results: From pre-policy to post-policy implementation period, communities in both waves experienced significant reductions in flavoured product availability (ranging from 27.2% to 50.9%), even after adjusting for community-level characteristics. In both waves 1 and 2, reductions in flavoured product availability were significantly greater compared with comparison communities during the same time frame, adjusting for community-level characteristics. Conclusions: Compliance with flavoured product restriction policies is high among tobacco retailers throughout Massachusetts, regardless of community demographic and retail characteristics. Reduced availability of flavoured tobacco in the retail environment has the potential to reduce youth exposure, access and use of these products.